Penyuluhan Hukum Mengenai Hak-Hak Tenaga Kerja Kontrak Kepada Anggota Konfederasi Serikat Buruh Sejahtera Indonesia (K-SBSI) Provinsi Riau - Suhendro; Miftahul Haq; Andrew Shandy Utama (Jurnal Mitra Pengabdian Farmasi, 2021)
The problem of partners in this community service activity is the lack of knowledge of members of Confederation of Prosperous Trade Union of Indonesia of Riau Province on protection of contract labor rights based on Law Number 13 of 2003 about Employment. The solutions offered in the public service activities are the improvement of K-SBSI members' knowledge of Riau province on the protection of the rights of labor contracts based on Law Number 13 of 2003 about Employment. The method of implementation of community service activities is by using lecture, dialogue, and discussion methods in order to provide legal counseling to partners. Participation of partners in community service activities is to provide time, provide a place with other supporting facilities, and present the community as participants of legal counseling. Output targets of community service activities are the publication of scientific articles in legal journals. The conclusion is that the community service has been successfully implemented and the benefits can be felt directly by the participants, which is to increase the knowledge of K-SBSI members of Riau Province regarding the protection of contract labor rights based on Law Number 13 of 2003 about Employment. This can be seen from the answers of the participants in the questionnaire given after the implementation of the activity. Of the 16 participants, 87.5% said they understood it.